Pediatric Diastolic Heart Failure: Clinical Features Description of 421 Cases - Pan, Bo; Hu, Di; Sun, Huichao; Lv, Tiewei; Xu, Wangguo; Tian, Jie (Frontiers in Pediatrics, 2022)
Background and Aim: Heart failure in children differs substantially from it in adult population. Clinical characteristics of pediatric diastolic heart failure has rarely been reported. In this study, we aimed to summary the causes, clinical features, lab tests and treatment effect of pediatric diastolic heart failure. Methods: This study was a single center, retrospective study conducted in Children’s Hospital of Chongqing Medical University. Children who were diagnosed with DHF without systolic heart failure (SHF) between 2006 to 2014 were included. Meanwhile, SHF (without DHF) cases were also collected from 2013 to 2014. Results: A total of 421 DHF and 42 SHF cases were included. The average age of pediatric DHF was 1.89±3.29 years old, significant younger than that of SHF (4.65±4.90). The top three cardiovascular causes of DHF were complex congenital heart malformations (53.4%), simple congenital heart defect (15.7%) and cardiomyopathy (7.4%). On the other side, number of cardiomyopathy cases (57.1%) ranked first in SHF group. Simple CHDs barely caused SHF. The most common symptom and sign were short breath and hepatomegaly in pediatric HF. Symptoms like cyanosis, feeding difficulty, be fidgety, pale, fatigue and edema were valuable in differential diagnosis of DHF and SHF in children. B-type natriuretic peptide (BNP) increase was found in 36.9% of DHF children, and 60% in SHF patients. Sensitivity of BNP greater than 100 pg/ml in diagnosis of DHF was 0.37, and specificity of it was 0.86. Diastolic function indicators, such as E/A ratio, IVRT were significant recovered after treatment in DHF patients. Less therapeutic benefits were achieved in children with cardiomyopathy induced DHF, in compared with non-cardiomyopathy patients. Conclusion: Pediatric DHF and SHF were largely different in primary causes, clinical symptoms and signs and short-term prognosis. There was a limit diagnostic value of BNP with 100pg/ml as cut-off value in pediatric DHF. Larger, multicenter studies of pediatric DHF are required in the future.